Improving Pupils' Conscience of Learning English Language Through Culture (JETLi: Journal of English Teaching and Linguistics, 2023)
Instead of being isolated, they are less successful now since they do not speak a second language. Spanish is where the proverb "a person who speaks two languages is worth two" originated. As a result, students who get insufficient second language instruction are unable to realize their full potential. This article aims to demonstrate the need to learn a second language, in this case, English, as well as how to communicate with people from other cultures in a natural manner while accepting and appreciating their range of emotions. Culture and language have many similarities. In addition to reflecting culture, language also shapes and is influenced by it. As a result, learning about the culture of the language is a part of teaching English.This paper demonstrates strategies for fostering multicultural awareness among English language learners. Teaching students about culture beyond food and national costume in an English language classroom may be difficult for any instructor. This article places a strong emphasis on the need for English teachers to be sensitive to their students' vulnerabilities by using strategies that promote intercultural understanding. It also offers a detailed explanation of the part that culture plays in teaching and learning English. Language is a component of culture and has a significant impact on how that culture develops. It is seen by some sociologists as the cornerstone of culture. They contend that culture could not exist without language. Language is shaped and affected by culture while it reflects it. Thus, culture has a significant role in language instruction, as the English teaching community generally agrees. The link between culture and language is illustrated in this paper.